Oligarki Media dalam Pusaran Pemilihan Presiden dan Wakil Presiden Republik Indonesia 2019 Menuju 2024 - Rembulan Randu Dahlia; Panji Anugrah Permana (Politicos: Jurnal Politik Dan Pemerintahan, 2022)
This study discusses the political aspects of the media oligarchy in the 2019 presidential election and analysis of the linkages that will emerge in the 2024 presidential election. The analysis in this study also criticizes the function of the press and the function of political parties which are tools of the oligarchy to gain power. This study uses a qualitative approach with case study methods, data collection techniques using interviews, observation and documentation. Then perform analysis in the form of data reduction, data presentation and drawing conclusions. The results showed that the media oligarchy in this study was Hary Tanoesoedibjo through MNC Media and the Partai Persatuan Indonesia became an important part in winning the candidates for President and Vice President of the Republic of Indonesia. Historically, Hary Tanoesoedibjo's political support showed a change in the 2014 Presidential Election in favor of Prabowo Subianto - Hatta Rajasa, while during the 2019 Presidential Election Hary Tanoe supported Joko Widodo-Ma'ruf Amin. On the basis of Hary Tanoesoedibjo's political support for the Joko Widodo-Ma'ruf Amin pair, the Partai Persatuan Indonesia received the position of Deputy Minister of Tourism and Creative Economy. The position of media oligarchs in the 2024 election is likely to remain in a favorable situation, because Indonesia does not yet have regulations regarding restrictions on political activities in the media or content that is closely related to creating positive framing of certain parties and candidates.